RATIO DECIDENDI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 49/PUU-X/2012 TENTANG PEMBATALAN PASAL 66 AYAT (1) UUJN-2004 - Hery Kurniawan Zaenal (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to: (1) analyze and find the ratio of the decision of the Constitutional Court Decision Number 49/PUU-X/2012 concerning the annulment of Article 66 paragraph (1) UUJN-2004, (2) the legal impact of the Constitutional Court's decision no. 49/PUU-X/2012 Against Legal Protection for Notaries. The type of research is normative law. While the research approach used, namely: Legislation, contextual approach, and case approach, as well as a comparative approach. The legal materials used in this study are primary legal materials and secondary legal materials. While the analysis of legal materials using qualitative analysis. The results of the study show that: (1) The ratio decidendi of the cancellation of Article 66 paragraph (1) of Law Number 30 of 2004 concerning the Position of Notary Public is based, that the article is not in accordance with the principle of equality before the law (equality in law) for every citizen. There is the approval of the Notary Honorary Council, not in accordance with the sense of justice and the criminal law enforcement process, as well as the principle of an independent judicial power; (2) Legal Impact of MK Decision No. 49/Puu-X/2012 Regarding Legal Protection for Notaries, the notary loses his special rights, namely summoning a Notary in the case of interest in a criminal examination does not need to obtain permission from the Regional Supervisory Council as stipulated in the provisions of Article 66 of the JN Law, this is for guarantee legal certainty and responsibility for the deed issued.